Plan de negocios para una microempresa de bebidas naturales artesanales en el cantón Latacunga, provincia de Cotopaxi. - Encalada Zurita, Mateo Sebastián (2024)
The main objective of this project was to develop a business plan for creating a microenterprise dedicated to producing natural handmade drinks in the city of Latacunga, province of Cotopaxi. The methodology used was quantitative-descriptive using the deductive method; the technique used was the survey using a questionnaire. A market study was carried out to find out the tastes and preferences of future customers according to their demands, allowing the expectations and satisfaction of consumers to be met. The population considered was segmented according to ages between 5 and 49 years old in the urban area of the city of Latacunga, with a population of 54,889 inhabitants, with a sample of 382 people to whom the surveys were applied in order to carry out the corresponding market study. The project's initial investment will be $59,756.91, which the shareholders' contribution will cover. The financial indicator analyzed for the project was the NPV, with a value of 55,341.21, which reflects the utility capital taken to present value. The IRR is 32.09%, which corresponds to the percentage of profit that the project yielded inflows; on the other hand, the Internal Recovery Period (IRP) calculated is one year, five months, and 12 days, and the cost-benefit is 1,391, which means that for every dollar invested, the investors earn 39 cents. Based on this analysis, it has been determined that the project is viable and profitable.